Structure selection and coordination in dual-channel supply chains - Jingjing Cai; Jing Wu; Meidan Xiao; Bin Liu; Wenliang Wang (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: This paper investigates the influence of channel structures and channel coordination on the supplier, the retailer and the entire supply chain in the context of two different kinds of marketing models: The common retailer and the exclusive shop. Methodology: With suppliers who manufacture the alternative commodities and retailers in the dual-channel supply chains as the object of the research, this paper compares suppliers' profits, consumer utility without coordination and contrasts suppliers' and retailers' profits with coordination to determine the range of the revenue sharing rates and which parameters are related. Findings: The analysis suggests the preference lists of the supplier and the retailer over channel structures with and without coordination are different, and depend on parameters like channel basic demand, channel cost and channel substitutability. Originality/value: In this research, new sales model for two suppliers should choose the same retailer or the exclusive retailers to sell their commodities.
Keywords: 650; supply chain selection; supply chain coordination; profits; Pareto zone